PENERAPAN MEDIA CHEMSCOOL DENGAN METODE GUIDED NOTE TAKING PADA PEMAHAMAN KONSEP SISWA - Prabowowati, Kartika; Hadisaputro, Subiyanto (Jurusan Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2014)
The study aims to determine the ability of studentsâ conceptual understanding after learning with Chemscool media and Guided Note Taking worksheet, and also to know students and teachers response to Chemscool media and Guided Note Taking worksheet used in the redox concept. The population in this study is X3-X5 grade in Senior High School in Magelang at academic year 2013/2014. By using cluster random sampling technique, it gained X3 as control class, X4 as a test class, and X5 as experiment class. Control variables in this study are studentsâconceptual understanding which the design of control-group pretest-posttest experimental. Aa preliminary analysis, the two groups have equal variance, normal distribution Â and the same of average value. Final analysis showed an increase in students conseptual understanding and a positive response from teachers and students. Based on the N-Gain test andÂ mastery learning test of experimental class got 75.25 % and 90.63 % and control class got 67.86 % and 78.13 %. The conclusions in this study: prove that learning with media Chemscool and Guided Note Taking worksheet can improve students conceptual understanding and Teachers and students gave positive responses to the media and worksheets. Â Keywords: Chemscool, Guided Note Taking, Conceptual UnderstandingÂ